Selective sample handling and detection in high-performance liquid chromatography. - Frei, R. W. (Roland W.); Zech, K. (Journal of chromatography library ;, 1989)
This is the second of a two-volume project which treats the handling, separation and detection of complex samples as an integrated, interconnected process. On the basis of this philosophy the editors have selected those contributions which demonstrate that optimal sample preparation leads to a simplification of detection or reduced demands on the separation process. Throughout the book emphasis is on chemical principles with minimum discussion of the equipment required - an approach which reflects the editors' view that the limiting factor in the analysis of complex samples is an incomplete knowledge of the underlying chemistry rather than the hardware available. This lack of knowledge becomes more evident as the demands for lower detection limits grow, as solving complex matrix problems requires a greater understanding of the chemical interaction between the substance to be analysed and the stationary phase. Thus, apart from one chapter dealing with chemically modified silicas, the main theme of the book is developed in three chapters on sample preparation and three on detection. The opening chapter outlines concentration and chromatography on chemically modified silicas with complexing properties, and gives examples of the use of these phases with organic and inorganic compounds. Chapter II, the first of the three contributions dealing with sample preparation, addresses such questions as whether the prepared sample is representative of the material to be analysed; how to avoid contamination; which separation procedure should be used to avoid tedious sample preparation. Chapter III describes the processing of whole blood for drug analysis. The determination of cyclosporine and its metabolites (an especially difficult case) demonstrates how comprehensive the optimisation of sample preparation must be to successfully perform the analysis. Several other examples are also given. Chapter IV deals with radio-column liquid chromatography and introduces the other theme of the book, i.e. selective detection methods. The widespread use of radioisotopes requires a high degree of purification during the manufacture of the compounds, as well as highly accurate detection methods in biological and biochemical studies. Chapter V continues the theme of selective detection with an overview of post-column reaction detection. The use of immobilised enzymes in post-column reactors or `pumpless' reactor systems for on-line reagent generation after the chromatographic separation step is discussed in detail. Various examples of the separation of biological compounds show how the production of electrochemical reagents and photochemical reaction detection have increased the selectivity of the detection, leading to more economical analytical systems. Selective detection employing luminescence detection techniques is outlined in Chapter VI. The use of immobilised fluorophores or the coupling to photochemical reactions leads to highly selective detection systems which can greatly simplify the sample handling. The final chapter reviews the use of continuous separation techniques in flow injection analysis thus revealing the need for a strong interdisciplinary dependence between sample handling and separation in this area. Written by experienced practitioners, this book will be extremely useful to investigators in many areas of application. Each chapter includes sufficient references to the literature to serve as a valuable starting point for more detailed investigation. The strong emphasis on sample handling makes the book unique in many ways and it will be welcomed by environmental scientists as well as those active in the clinical, pharmaceutical and bioanalytical fields.